2015
DOI: 10.1016/j.polymer.2014.11.035
|View full text |Cite
|
Sign up to set email alerts
|

Structure and blood compatibility of highly oriented poly(l-lactic acid) chain extended by ethylene glycol diglycidyl ether

Abstract: Highly-oriented poly(L-lactic acid) (PLLA) were fabricated through chain extension with ethylene glycol diglycidyl ether (EGDE) and solid hot drawing technology.The extending degree as high as 25.79 mol% can be obtained at 0.7wt% EGDE content. The complex viscosity, storage and viscous modulus for chain extended PLLA were improved resulting from the enhancement of molecular entanglement, and consequently higher draw ratio can be achieved during hot stretching. The tensile strength and modulus of PLLA were impr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 46 publications
0
19
0
Order By: Relevance
“…As shown in Figure (a), only a few dispersed adhered platelets were observed, and they showed a round shape with no pseudopodia; this means that there may have been no platelet activation. Then, the platelet adhering number was calculated from scanning electron microscopy images and compared with those of other blood‐contacting polymers in Figure (b) . The relatively low value of PVC‐40 revealed that the platelet adhesion was greatly suppressed on the PVC‐40 surface.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Figure (a), only a few dispersed adhered platelets were observed, and they showed a round shape with no pseudopodia; this means that there may have been no platelet activation. Then, the platelet adhering number was calculated from scanning electron microscopy images and compared with those of other blood‐contacting polymers in Figure (b) . The relatively low value of PVC‐40 revealed that the platelet adhesion was greatly suppressed on the PVC‐40 surface.…”
Section: Resultsmentioning
confidence: 99%
“…Samples about 10 mg were heated under nitrogen atmosphere from room temperature to 200°C with the heating rates were 10°C/min. Then, X c can be calculated as follow: Xc=()normalΔHm/normalΔH0×100% where Δ H m was the melting enthalpies for the samples; Δ H 0 was the melting enthalpies for 100% crystalline PLA. The Δ H 0 of PLA was 93 J/g.…”
Section: Methodsmentioning
confidence: 99%
“…Samples about 10 mg were heated under nitrogen atmosphere from room temperature to 200 C with the heating rates were 10 C/min. Then, X c can be calculated as follow 18 :…”
Section: Measurementsmentioning
confidence: 99%
“…Granulated samples of about 10 mg were heated from ambient temperature to 200 o C at a constant rate of 10 K/min under nitrogen atmosphere. Xc can be calculated with the following equation [13]:…”
Section: Non-isothermal Crystallization Analysismentioning
confidence: 99%